PENGARUH PELATIHAN BEBAN LEG PRESS TERHADAP KECEPATAN LARI DAN DAYA LEDAK OTOT TUNGKAI - Mahayasa Hadiwijaya, Made (Jurnal Ilmu Keolahragaan Undiksha, 2013)
The aim of this study to determine the effect of weight training on leg press towards running speed and explosive power leg muscle. Type of this research is real experimental (true experimental) with draft of The Randomized Pretest-Posttest Control Group Design. 60 samples from class X of SMK Negeri 1 Singaraja school year 2012/2013 are determined by random sampling technique. Running speed was measured with a 50 meters sprint test and leg muscle explosive power measured by the vertical jump test, then the data were analyzed by independent t-test at significance level (α) of 0.05. Calculated significance value smaller than the value of α (0.05), thus the research hypothesis "leg press weight training affects the running speed and explosive power of the leg muscles" acceptable. From the results of this study concluded that: (1) leg press weight training affect men's running speed class X students of SMK Negeri 1 Singaraja school year 2012/2013. (2) training load effect on the leg press leg muscle explosive power class X student son SMK Negeri 1 Singaraja school year 2012/2013. Recommended for sports people (coaches, trainers, athletes and gym teacher) to use the leg press weight training as an alternative to increasing running speed and explosive power leg muscle.